Cystic neuroblastoma in an infant: A case report - Bajracharya, Jasmine; Upadhyay, Sagar; Poudel, Prabhat; Khadka, Binay (Journal of Society of Surgeons of Nepal, 2022)
Neuroblastoma is a neoplasm of the peripheral sympathetic nervous system. Depending upon the primary location of the tumor, it can present as incidental finding, hypertension, abdominal pain, and distention with nonspecific clinical signs. Our patient was four-months-old when he developed excessive crying, increased frequency of micturition, and loose bowel movements. On CT scan, a cystic mass was found in the left suprarenal region and was surgically removed. Immunohistochemistry of the mass confirmed the diagnosis of cystic neuroblastoma. The outcome was good after surgical excision and chemotherapy. Early diagnosis and management of cystic neuroblastoma will result in a good outcome.